DOI: 10.33915/etd.3640
|View full text |Cite
|
Sign up to set email alerts
|

Crisis as Opportunity: Personality Constructs and Erikson Identity Development

Abstract: Identity development theory suggests that the developmental trajectory from childhood through young adulthood involves a movement from exploration towards eventual tentative commitment to adult values, beliefs, and career goals. Currently little research has focused on the impact of personality traits commonly studied in personal counseling and career work with collegeattending emerging adults on the process of identity development. This study examined the predictive quality of personality preferences on Erick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 131 publications
(267 reference statements)
0
2
0
1
Order By: Relevance
“…Orijinal formunun (Luyckx ve ark., 2008a) ise hem ergenler hem de beliren yetişkinler üzerinde yapıldığı KGBÖ'nün, Türkçe uyarlamasının yalnızca ergenler üzerinde gerçekleştirildiği görülmektedir (Morsünbül, 2011;Morsünbül ve Çok, 2014). Ancak kimlik biçimlenmesi beliren yetişkinlik döneminde de şekillenmeye devam ettiğinden (Cookston ve Remy, 2015;Ruth, 2013), bu çalışma beliren yetişkinlere odaklanarak kimliğin ölçümüne ilişkin incelemelerde bulunmuştur. Dolayısıyla bu çalışma, hem beliren yetişkinlik dönemindeki kadınlara hem de okul dışı katılımcılara dönük bir ölçme aracı sağlama açısından önemlidir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Orijinal formunun (Luyckx ve ark., 2008a) ise hem ergenler hem de beliren yetişkinler üzerinde yapıldığı KGBÖ'nün, Türkçe uyarlamasının yalnızca ergenler üzerinde gerçekleştirildiği görülmektedir (Morsünbül, 2011;Morsünbül ve Çok, 2014). Ancak kimlik biçimlenmesi beliren yetişkinlik döneminde de şekillenmeye devam ettiğinden (Cookston ve Remy, 2015;Ruth, 2013), bu çalışma beliren yetişkinlere odaklanarak kimliğin ölçümüne ilişkin incelemelerde bulunmuştur. Dolayısıyla bu çalışma, hem beliren yetişkinlik dönemindeki kadınlara hem de okul dışı katılımcılara dönük bir ölçme aracı sağlama açısından önemlidir.…”
Section: Discussionunclassified
“…Bu ölçme aracının farklı kavramlarla incelenmesi kadınlarda kimlik biçimlenmesinin daha iyi anlaşılmasına olanak sağlayacağı gibi, süreç odaklı çalışmalara da katkıda bulunacaktır. identity development continues to take shape in the emerging adulthood (Ruth, 2013) and it is suggested that identity development may be different in women (Erikson, 1994;Gilligan, 2017), it is considered appropriate to repeat the psychometric analysis of the scale on young women. This study is important in terms of providing a measurement tool for both women and out-of-school participants in order for researchers to reach out to different people in the region and examine their identity functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation